Quercetin suppresses ROS production and migration by specifically targeting Rac1 activation in gliomas - Baba, Rafia A.; Mir, Hilal A.; Mokhdomi, Taseem A.; Bhat, Hina F.; Ahmad, Ajaz; Khanday, Firdous A. (Frontiers in Pharmacology, 2024)
P66Shc and Rac1 proteins are responsible for tumor-associated inflammation, particularly in brain tumors characterized by elevated oxidative stress and increased ROS production.Quercetin, a natural polyphenolic flavonoid is a well-known redox modulator with anti-cancer properties. It has the capacity to cross the blood-brain barrier and thus could be a possible drug against brain tumors. In this study, we explored the effect of Quercetin on Rac1/p66Shc mediated tumor cell inflammation, which is the principal pathway for the generation of ROS in brain cells. Glioma cells transfected with Rac1, p66Shc, or both were treated with varying concentrations of Quercetin for different time points. Quercetin significantly reduced the viability and migration of cells in a ROS-dependent manner with concomitant inhibition of Rac1/p66Shc expression and ROS production in naïve as well as Rac1/p66Shc transfected cell lines, suggestive of preventing Rac1 activation. Through molecular docking simulations we observed that Quercetin showed the best binding compared to other known Rac1 inhibitors and specifically blocked GTP binding site in the A-loop of Rac1 to prevent GTP binding and thus Rac1 activation. We conclude that Quercetin exerts its anti-cancer effects via modulation of Rac1-p66Shc signaling by specifically inhibiting Rac1 activation thus restraining production of ROS and tumor growth.